Gnss interference, threats, and countermeasures - Dovis, Fabio (Technology and applications, 2015)
Reliable positioning and navigation is becoming imperative in more and more applications for public services, consumer products, and safety-critical purposes. Research for finding pervasive and robust positioning methodologies is critical for a growing amount of societal areas while making sure that navigation is trustworthy and the risks and threats of especially satellite navigation are accounted for. This book provides a comprehensive survey of the effect of radio-frequency interference (RFI) on the Global Navigation Satellite Systems (GNSS) as well as of the spoofing threats.Through case studies and practical implementation/applications, this resource presents engineers and scientists with a better understanding of interference and spoofing threats, ultimately helping them to design and implement robust systems